Estratégias de marketing de relacionamento da Rede Sinodal de Educação: a relação entre as expectativas e a percepção da qualidade em serviços - Ergang, Sandro (2007)
The educational environment has presented in recent years one high degree of competitiveness, the incited competition and the increasing demand for a great variety of courses have motivated the education institutions to invest in solutions to know its students better and to interact more with them in directed way. Studies indicate, that the student in moment of the decision for an institution or the other, take in consideration the experience and the knowledge concerning this, through research with known friends and. To become the student a potential advertiser, very requires effort in relationship marketing, in offers of the package of educational services. The area of study of the quality in services, points the SERVQUAL used in this study, as a tool capable to provide to a necessary diagnosis on expectative and perceptions concerning the educational services. On the basis of these abilities presented for the methodologies, a significant sample of students of the Instituto Superior de Educação of Rede SINODAL was determined, to verify and to prove advantages and competitive deficiencies of these IES, to make possible the concentration of efforts in the relationship, as much in the current studies how much for prospect. The results of this instrument study will be able to serve as a significant pointer for managing Institutions of Education that they intend to identify necessary areas of improvement in the package of the educational service and to the investigators that look an instrument of measurement of the quality in services.